Jewish, Christian, and Classical Exegetical Traditions in Jerome's Translation of the Book of Exodus : Translation Technique and the Vulgate. - A. Kraus, Matthew. (Vigiliae Christianae, Supplements, 2017)
In Jewish, Christian, and Classical Exegetical Traditions in Jerome's Translation of the Book of Exodus: Translation Technique and the Vulgate , Matthew Kraus offers a layered understanding of Jerome's translation of biblical narrative, poetry, and law from Hebrew to Latin. Usually seen as a tool for textual criticism, when read as a work of literature, the Vulgate reflects a Late Antique conception of Hebrew grammar, critical use of Greek biblical traditions, rabbinic influence, Christian interpretation, and Classical style and motifs. Instead of typically treating the text of the Vulgate and Jerome himself separately, Matthew Kraus uncovers Late Antiquity in the many facets of the translator at work-grammarian, biblical exegete, Septuagint scholar, Christian intellectual, rabbinic correspondent, and devotee of Classical literature.